Cord Care Practices: A Perspective of Contemporary African Setting - Tolulope O. Afolaranmi; Tolulope O. Afolaranmi; Zuwaira I. Hassan; Zuwaira I. Hassan; Ofakunrin O. Akinyemi; Ofakunrin O. Akinyemi; Sarah S. Sule; Matthew U. Malete; Choji Pam Choji; Danjuma A. Bello; Danjuma A. Bello (Frontiers Media S.A., 2018)
BackgroundCord care is the series of steps applied in handling of the umbilical cord after delivery of the new born. Globally, an estimated 4 million deaths occur annually within the first 4 weeks of life and 1.5 million of these deaths are attributable to infections. In Nigeria, studies have reported umbilical cord infections accounting for between 10 and 19% of neonatal admissions and resultant estimated 30-49% neonatal deaths. Hence, this study was conducted to assess the knowledge and practice of cord care within a contemporary setting.MethodologyThis was a cross-sectional study conducted among 324 mothers of children less than 59 months using a multistage sampling technique and SSPS version 20 was used for data analysis. Crude and adjusted odds ratios as well as 95% confidence interval were used in this study with a P-value of ≤0.05 considered statistically significant.ResultsThe mean age of the mothers in the study was 27.5 ± 6 years with majority of them having good overall knowledge and practice of cord care. Factors such residence in rural community (AOR = 0.26; 95% CI = 0.0915-0.7230) and heath facility delivery (AOR = 7.0; 95% CI = 4.7877-9.3948) were predictors of cord care practices.ConclusionThis study has brought to light the level of cord care practices with health facility delivery, place of residence, and knowledge of cord care as its determinants.